201 Intraoperative Cerebral Glioma Characterization With Contrast Enhanced Ultrasound. Issue Volume 61:Issue CN Supp. 1(2014)Supplement (1st August 2014) - Prada, Francesco; Mattei, Luca; Filippini, Assunta; Casali, Cecilia; Legnani, Federico G.; Moiraghi, Alessandro; Perin, Alessandro; Richetta, Carla; Vetrano, Ignazio G.; DiMeco, Francesco
Abstract: INTRODUCTION: Contrast enhanced ultrasound (CEUS) is a dynamic and continuous modality that offers a real-time direct view of vascularization and flow distribution patterns of different organs and type of tumors. Nevertheless, its intraoperative use for brain tumors visualization has been performed few times, and there are no guidelines on this regard. Furthermore, a thorough characterization of cerebral glioma had never been performed. The main aim of the study is to describe the different patterns of enhancement of cerebral gliomas using the CEUS technique. METHODS: We performed intraoperative CEUS (iCEUS) in an off-label setting in 69 patients undergoing surgery for cerebral glioma. Ultrasound contrast agent (UCA) (sulphur hexafluoride (SonoVue—Bracco—Italy)) was administered intravenously and the lesion scanned for at least 120 seconds. An on-site and a post-procedural semi-quantitative analysis was performed for each case, evaluating CEUS parameters, following the guidelines of the European Federation for Ultrasound in Medicine and Biology (EFSUMB): timing, degree of CE and contrast distribution. RESULTS: Both low-grade glioma (LGG) and high-grade glioma (HGG) appear hyper-echoic relative to the adjacent brain parenchyma on B-mode US. Different contrast enhancement patterns were observed according to lesion characteristics: LGG showed a dotted or diffuse appearance with a slower and delayed arterial and venous phase compared with HGG, whereas HGG have a more nodular, non-homogeneous appearance, with faster and major contrast enhancement. CONCLUSION: Our study characterizes for the first time, human brain glioma with iCEUS, giving us further insight regarding the biology of these tumors: being a dynamic and continuous modality it offers a real-time direct view of the tumor perfusion and of the afferent and efferent vessels. CEUS is a fast, safe, dynamic, real-time, economic tool that might be helpful during surgery in differentiating malignant and benign gliomas and refining the surgical strategy.